Cnidarian peptide neurotoxins: a new source of various ion channel modulators or blockers against central nervous systems disease. Issue 1 (January 2019) - Liao, Qiwen; Feng, Yu; Yang, Binrui; Lee, Simon Ming-Yuen
Highlights: Peptide toxins are potential drug leads owing to high potency and selectivity. The neurotoxins from cnidaria could modulate or block against the ion channels. Neurotoxin presents with analgesic, antiepileptic or neuroprotective effects. Neurotoxin attracts interest in drug development for neurological disorders. Abstract : Cnidaria provide the largest source of bioactive peptides for new drug development. The venoms contain enzymes, potent pore-forming toxins and neurotoxins. The neurotoxins can immobilize predators rapidly when discharged via modifying sodium-channel-gating or blocking the potassium channel during the repolarization stage. Most cnidarian neurotoxins remain conserved under the strong influence of negative selection. Neuroactive peptides targeting the central nervous system through affinity with ion channels could provide insight leading to drug treatment of neurological diseases, which arise from ion channel dysfunctions. Although marine resources offer thousands of possible peptides, only one peptide derived from Cnidaria: ShK-186, also named dalazatide, has reached the pharmaceutical market. This review focuses on neuroprotective agents derived from cnidarian neurotoxic peptides.